Hour of the gun [videorecording (DVD)] - Anhalt, Edward, 1914-2000; Garner, James, 1928-2014; Robards, Jason; Ryan, Robert, 1909-1973; Salmi, Albert; Aidman, Charles; Ihnat, Steve, 1934-1972; Ballard, Lucien, 1908-1988; Goldsmith, Jerry (Metro-Goldwyn-Mayer Studios, 2023)
When the Clanton gang kills Wyatt Earp's brothers, he decides to go after them and enlists the help of his friend Doc Holliday.